PENINGKATAN HASIL BELAJAR SISWA MELALUI MEDIA PEMBELAJARAN SITARA PADA MATA PELAJARAN IPAS KELAS V SEKOLAH DASAR - Saskia Putri, Andin; Lutfauziah, Asmaul; Ibrahim, Muslimin; Mustofa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine the improvement of students' learning outcomes through the use of Sitara learning media in science and social studies (IPAS) and to identify students' responses toward its implementation. This quantitative study employed a pre-experimental one-group pretest-posttest design involving 25 fifthgrade students at SD Sidoarjo. Data were collected through learning achievement tests and student response questionnaires. The data were analyzed using the Shapiro-Wilk normality test and paired sample t-test. The results showed that the average pretest score of 55.4 increased to 88.8 in the posttest. The paired sample t-test indicated a significance value of 0.000 (p<0.05), suggesting a significant difference before and after the implementation of Sitara learning media. Students' responses reached an average percentage of 88%, categorized as very good. Therefore, Sitara learning media can be used as an innovative alternative to improve elementary students' learning outcomes in IPAS.